THE EFFECT OF UNDERSTANDING TAX REGULATIONS ON E-COMMERCE TRANSACTIONS ON TAXPAYER COMPLIANCE (Case Study on E-Commerce Business Owners in West Java) - Santi Mita Niar; Apriwandi Apriwandi (SEAN Institute, 2023)
The purpose of this study was to investigate the relationship between better taxpayer compliance and understanding of the tax laws governing online transactions. Internet shop owners in West Java constituted the entire research population. One hundred online shop owners became the sample selected by the researcher using a technique called purposive sampling. Data collection techniques through surveys. Data analysis techniques combine traditional assumption tests with direct regression analysis. The findings of this study indicate that understanding tax regulations has a favorable and significant impact on taxpayer compliance because taxpayers will more easily understand and comply with tax requirements if they are more familiar with them.